A CASE OF LATE-ONSET HYPOPARATHYROIDISM FOLLOWING RECURRENT ANTERIOR NECK SURGERY RESULTING IN RHABDOMYOLYSIS - Lim, Guat Yee; Tan, Florence (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hypoparathyroidism is a known complication of anterior neck surgery, with 1.5% becoming permanent. Delayed-onset hypoparathyroidism can manifest years postoperatively due to progressive scar tissue formation. It is often overlooked, causing complications. We present such a patient complicated by rhabdomyolysis and renal failure. CASE A 78-year-old female with poorly-controlled diabetes mellitus presented with recurrent episodes of generalized weakness, lethargy and gastrointestinal symptoms since March 2024. She had undergone a total thyroidectomy in 2009 for multinodular goiter and neck surgery in 2022 for extensive neck abscess. Her calcium was normal in 2019 but no other postoperative monitoring was done. She was admitted in March, May, and September 2024 with increasing myalgia, breathlessness, elevated creatine kinase (CK) (500 to 3000 U/L) and progressive renal dysfunction [creatinine: 93 mmol/L (March), 175 mmol/L (May), 422 mmol/L (September)]. Thyroid function tests were normal. Urinalysis showed proteinuria and hematuria. Extensive investigations for autoimmune myositis and renal failure were unremarkable, resulting in a presumed diagnosis of diabetic nephropathy. In September, amid worsening renal function and persistent CK elevation, severe hypocalcemia (1.30 mmol/L*) was finally recognized. Retrospectively, hypocalcemia (1.47 mmol/L) was first detected in May 2024, treated with intravenous calcium bolus, but not investigated. Immediate calcium infusion with oral calcium and calcitriol supplementation led to a significant CK reduction from 1233 U/L to 286 U/L, creatinine level decreased from 422 mmol/L to 315 mmol/L, with marked improvement of her symptoms and she was discharged without residual weakness. Subsequent follow-up showed further improvement in creatinine to 187 mmol/L and a stabilized CK level (235 U/L). Ultimately, hypoparathyroidism was confirmed to have an undetectable iPTH level. CONCLUSION This case highlights the importance of recognizing delayed hypoparathyroidism and its presentation with severe rhabdomyolysis. Unawareness of this complication and a low index of suspicion can lead to prolonged misdiagnosis and exacerbate complications. Prompt recognition and treatment are crucial.